2019
DOI: 10.1017/qua.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

East Asian summer monsoon climates and cave hydrological cycles over Dansgaard-Oeschger events 14 to 11 revealed by a new stalagmite record from Hulu Cave

Abstract: A 230Th/U-dated stalagmite from Hulu Cave was analyzed for δ18O, δ13C, and trace elements. A ~10-yr-resolution δ18O record, spanning 51.7–42.6 ka, revealed Dansgaard-Oeschger (DO) events 14 to 11. A similar rapid transition and synchronous timing of the onset of DO 12 is evident between the Greenland and Hulu Cave records, which suggests a common forcing mechanism of DO cycles in the North Atlantic and monsoonal region of Asia. Centennial-scale monsoonal oscillations in the cave δ18O record are indicative of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…DOs have a global impact, but the magnitude and direction of change can be regionally variable (Sánchez Goñi and Harrison, 2010;Wolff et al, 2010). For example, more humid conditions are observed in the Mediterranean (Budsky et al, 2019), precipitation changes occur in South America (Zhang Y. et al, 2017) and East Africa (Brown et al, 2007), the monsoonal system intensifies in Asia (Li et al, 2017;Dong et al, 2018;Liang et al, 2019) and shifts in northwest Africa (Itambi et al, 2009), drying occurs in northern Australia (Muller et al, 2008) and Indonesia (Griffiths et al, 2013), and while other records suggest very little or no climatic fluctuations occurred during DOs (Mulitza et al, 2007;Hessler et al, 2010).…”
Section: Abrupt Climate Variabilitymentioning
confidence: 99%
“…DOs have a global impact, but the magnitude and direction of change can be regionally variable (Sánchez Goñi and Harrison, 2010;Wolff et al, 2010). For example, more humid conditions are observed in the Mediterranean (Budsky et al, 2019), precipitation changes occur in South America (Zhang Y. et al, 2017) and East Africa (Brown et al, 2007), the monsoonal system intensifies in Asia (Li et al, 2017;Dong et al, 2018;Liang et al, 2019) and shifts in northwest Africa (Itambi et al, 2009), drying occurs in northern Australia (Muller et al, 2008) and Indonesia (Griffiths et al, 2013), and while other records suggest very little or no climatic fluctuations occurred during DOs (Mulitza et al, 2007;Hessler et al, 2010).…”
Section: Abrupt Climate Variabilitymentioning
confidence: 99%
“…However, whether it indicates the spatial difference in soil moisture (or precipitation) between the northern and southern China, on the millennial scale, needs further confirmation by more geological records and simulation work. Dong et al, 2015), Dragon (DG, Dong et al, 2018a), Shizi (SZ, Zhou et al, 2009), Yongxing (YX, S. , Hulu (HL, Wang et al, 2001;Liang et al, 2019), Yangkou (YK, Han et al, 2016;T.-Y. Li et al, 2017), Xiaobailong (XBL, Cai et al, 2006) and Moomi Caves (Burns et al, 2003), and Arabian Sea sediment record (black dot, Deplazes et al, 2013) Svensson et al, 2008), stalagmite δ 18 O from Hulu Cave (D, back, Wang et al, 2001;magenta, Liang et al, 2019), δ 18 O from Yongxing Cave (E, S. , JFYK7 δ 18 O from Yangkou Cave (F, Han et al, 2016;T.-Y.…”
Section: Discussionmentioning
confidence: 99%
“…On account of lacking the full data coverage to the CIS14 range, above out of (or anti-) phase relationship of rainfall, between Jiang-Huai region (Hulu Cave) and northern China (Baiyun Cave), is still an open question. However, from the longer data at back (to 42.5 ka), these decoupling phases between the δ 13 C and trace elements and the δ 18 O seems to hold true (Liang et al, 2019). And the possible mechanisms are proposed below.…”
Section: Inverse Hydroclimate Footprints In Northern and Southern Chinamentioning
confidence: 92%
“…For example, Novello et al [15] determined the relationship between local hydroclimate and atmospheric convective processes related to the South American Monsoon System through a comparative study of speleothems δ 13 C and δ 18 O. With further studies of speleothem δ 13 C, more research has suggested that δ 13 C records can be employed to reflect hydroclimate variation by excluding the isotope kinetic fractionation process [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, stalagmite δ 13 C may respond to millennial climate changes more sensitively than stalagmite δ 18 O. The oxygen and carbon isotope records of stalagmites in China show millennial-time-scale oscillations, for instance, some records from Hulu Cave [20,22]. Other records from stalagmites in southern China show that the amplitude of millennial-time-scale events recorded by δ 13 C is twice as large as that of the δ 18 O record during the last two glacial cycles [22,23].…”
Section: Introductionmentioning
confidence: 99%